2013
DOI: 10.1093/humrep/det330
|View full text |Cite
|
Sign up to set email alerts
|

Copper T380 intrauterine device for emergency contraception: highly effective at any time in the menstrual cycle

Abstract: The original study was funded by the UNDP/UNPFA/WHO/World Bank Special Programme of Research, Development and Research Training in Human Reproduction. The donors and sponsors of the study had no role in the study design, data collection, data analysis, data interpretation, writing of the report or the decision to submit the paper for publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 13 publications
0
36
0
3
Order By: Relevance
“…8 Copper IUDs can even be resorted to as an emergency contraceptive method within 120 hours of unprotected intercourse. 9 Depot medroxy progesterone acetate (DMPA) is MEC category 2 1 due to its variable effect of decreasing bone mineral density. Progestin only pills, low dose combined hormonal contraception, contraceptive patch and contraceptive ring can also be used (MEC category 1 1 ) along with barrier methods (dual protection).…”
Section: Choice Of Contraception For Adolescentsmentioning
confidence: 99%
“…8 Copper IUDs can even be resorted to as an emergency contraceptive method within 120 hours of unprotected intercourse. 9 Depot medroxy progesterone acetate (DMPA) is MEC category 2 1 due to its variable effect of decreasing bone mineral density. Progestin only pills, low dose combined hormonal contraception, contraceptive patch and contraceptive ring can also be used (MEC category 1 1 ) along with barrier methods (dual protection).…”
Section: Choice Of Contraception For Adolescentsmentioning
confidence: 99%
“…While these calculations reflect current recommendations of the World Health Organization and other professional bodies, [19][20][21] such as Faculty of Sexual and Reproductive Healthcare ([FSRH] UK) and the Centers for Disease Control and Prevention (USA), they were challenged in a recent study 22 that suggests that the IUD is as safe and effective as emergency contraception whenever it is inserted in the menstrual cycle, provided a suitably sensitive pregnancy test is negative. This statement is based on the finding that there were no pregnancies in a group of women who had the IUD inserted outside the conventional "safe window".…”
Section: Mckay and Gilbertmentioning
confidence: 99%
“…In a systematic review of studies of the IUD for EC, five studies reported IUD insertions up to 10 days and beyond unprotected intercourse, and reported no pregnancies in that cycle among 732 women for whom follow-up information was available [58]. Table 2 contains a description of these studies, together with a secondary analysis of an additional study specifically looking at timing of insertion [116], and includes information on the number of women with IUD insertions beyond 5 days after unprotected intercourse. While the number of women outside the 5-day window was small in these studies, and further studies would be beneficial, the IUD appears to maintain its efficacy for EC beyond this period.…”
Section: Timing Of Iud Insertionmentioning
confidence: 99%